فعالية السياسة المالية في جذب الاستثمار الأجنبي المباشر في الجزائر - جيلي, ادريس; عاشور, الصادق; غدير احمد, خالد (جامعة الوادي university eloued, 2017)
يعتبر الاستثمار الأجنبي المباشر من أهم مصادر التمويل الخارجي، وذلك من خلال الخصائص التي يتميز بها كإدخال التكنولوجيا، وتحسين أساليب الإدارة. ولجذب هذا النوع من الإستثمار يجب إتباع مجموعة من السياسات، من أهمها السياسة المالية. من هنا تأتي أهمية هذه الدراسة، لمعرفة فعالية السياسة المالية في جذب الإستثمار الأجنبي المباشر في الجزائر خلال الفترة ( 1995-2015)، حيث تناولنا فيها الأسس النظرية للسياسة المالية والاستثمار الأجنبي المباشر والعلاقة بينهما، ثم تعرفنا عن السياسة المالية المتبعة في الجزائر والتحفيزات المقدمة، ثم تطرقنا بعد ذلك إلى واقع مناخ الاستثمار في الجزائر، وفي الأخير قمنا بدراسة قياسية لأثر السياسة المالية في جذب الإستثمار الأجنبي المباشر. ومن خلال هذه الدراسة توصلنا إلى النتائج التالية: 1. إن الزيادة في نفقات التجهيز، ساهمت في توفير بيئة جاذبة للاستثمار الأجنبي المباشر، وهذا ما أكدته الدراسة القياسية التي أثبتت وجود علاقة طردية بينهما. 2. إن تقديم إعفاءات وتحفيزات جبائيه ساهمت في توفير بيئة جاذبة للاستثمار الأجنبي المباشر، وهذا ما أكدته الدراسة القياسية التي أثبتت وجود علاقة عكسية بينهما Foreign direct investment is one of the most important sources of external financing, with characteristics such as the introduction of technology and the improvement of management methods. To attract this kind of investment, a set of policies must be pursued, the most important of which is fiscal policy. Hence, the importance of this study is to study the effectiveness of fiscal policy in attracting foreign direct investment in Algeria during the period 1995-2015, where we discussed the theoretical foundations of the policy of finance and foreign direct investment and the relationship between them. Then we learned about the fiscal policy in Algeria and the incentives provided, We then discussed the reality of the investment climate in Algeria, and in the end we conducted a standard study of the impact of fiscal policy in attracting foreign direct investment. Through this study we reached the following results: 1. The increase in processing expenses contributed to the creation of an attractive environment for foreign direct investment, which was confirmed by the standard study which proved a positive relationship between them. 2. The provision of exemptions and incentives to the military contributed to providing an attractive environment for foreign direct investment, as confirmed by the standard study, which proved an inverse relationship between them.
مذكرة ماستر اقتصاد عمومي
Keywords: الاستثمار، الاستثمار الأجنبي المباشر، مناخ الاستثمار، السياسة المالية، النفقات العامة، الايرادات العامة; investment, foreign direct investment, investment climate, fiscal policy, public expenditure, public revenue.